(untitled) (The Research of Medical Science Review, 2025)
Background: Osteoporosis is a common disease characterized by a systemic impairment of bone mass due to the deficiency of Vitamin D, which results in fragility fractures. Osteoporosis poses unique challenges for pregnant individuals, necessitating specialized care to ensure maternal and fetal well-being. Aim:The conduct study is representing the idea in comprehensive literature research and evidence-based interventions, especially in Pregnant women and worsens the lifestyle of their wellbeing to reduce the risk of fracture and improve bone health during pregnancy. Methodology:This study analyzes the complex relations between pregnancy and osteoporosis, highlighting the demand for individualized treatment strategies. The factors examined were physiological alterations, hormonal swings, and probable side effects of this dual diagnosis. The conducted research was divided in two parts in which detailed review of the literature of last 5 years and using that evidence the cross-sectional survey was implemented. The study offers evidence-based therapies such as dietary supplements, exercise advice, and medication. Result:The evaluated results show that 60% of the random women who participated in survey were found to be deficient in Vitamin D. This was comparable to the percentages of pregnant women (53%) and nursing moms (58%), respectively, who were Vitamin D deficient. Additionally, our study revealed that Vitamin D shortage in mothers increases the likelihood of neonatal Vitamin D deficit and puts nursing moms at a higher risk of developing osteoporosis. Conclusion:By addressing this under-researched intersection, healthcare providers can enhance the quality of care for pregnant individuals with osteoporosis, safeguarding both maternal and fetal health.